2017
DOI: 10.1016/j.jtcvs.2017.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, readmissions, and costs in transfemoral and alterative access transcatheter aortic valve replacement in the US Medicare population

Abstract: For patients ineligible to receive TF TAVR, TAO and TA approaches offer similar clinical outcomes at similar cost with acceptable operative and 1-year survival, except for higher rates of CPB use in TA patients. CPB was associated with worse survival and increased costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
(49 reference statements)
1
14
0
1
Order By: Relevance
“…It also supports the fact that Medicare reimbursement is often used as a proxy for health sector costs under the assumption that Medicare reimbursement is set at a level such that providers make minimal long-run economic profit (26). For future research, a costcenter–specific CCR is recommended to estimate costs of inpatient care more accurately (25).…”
Section: Discussionmentioning
confidence: 99%
“…It also supports the fact that Medicare reimbursement is often used as a proxy for health sector costs under the assumption that Medicare reimbursement is set at a level such that providers make minimal long-run economic profit (26). For future research, a costcenter–specific CCR is recommended to estimate costs of inpatient care more accurately (25).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare TF-TAVI with TAo-TAVI because the latter group is ineligible for femoral access. It is possible that such a study might favor the TAo-TAVI technique even in TF patients, 3 as recently reported. 9 Alternatively, TAo-TAVI patients who are ineligible for TF-TAVI can be evaluated against the outcomes of surgical aortic valve replacement.…”
mentioning
confidence: 81%
“…1 The transapical approach, the initial technique described for TAVI, has declined in use compared with the transfermoral (TF) approach and newer, alternative routes. This may be attributed to the emergence of downsized delivery systems and to the more relevant role of the alternative routes (eg, axillary artery, carotid artery, and direct aortic approaches), 2,3 during the past decade.…”
mentioning
confidence: 99%
“…14, 16-18 Because such prospective payments are based on average resource use this leads to loss of cost variability and precision across patients. 17-20 In some instances, patient level claims data are used, which capture both resource use and associated charges, 13-16, 21 however, such charges need to be converted to costs (i.e., the actual value of the resources consumed), which can be accomplished using institution specific cost-to-charge ratios (obtainable from CMS hospital cost reports). 13-16, 21-23 When charges are available at a cost center or department level (e.g.…”
Section: Estimation Of Costsmentioning
confidence: 99%